Gravações Encontradas - Exploração no contexto de performance de música electroacústica - Carla Mariana Arteaga do Nascimento Osório Sardon (2017)
Found recordings, as the name suggests, involve a concern for memory and personal files, through fragments of audio left by unknown people, on microcassette recorders.Personal interest in the characteristics of magnetic tape sound and its history in electroacoustic music is the main motivation of this project, but there is a choice of working the universe of pocket recorders and call recorders, delimiting research conceptually and from the technical point of view.The raw material of the practical component of this dissertation are the recordings found in these devices, acquired at fairs and second-hand stores. Its origin is always unknown, although in some cases, it is possible to identify temporal and physical spaces.It proposes here an analysis of the contents but also a creative experimentation with some of these recordings and devices of reading of magnetic tape, from techniques of cut, repetition (loop), modification of the speed of reading, as well as the mixture with other sources and effects Of audio, in the sense of developing an electroacoustic music performance.This research therefore involves the practice of hardware hacking and the construction of electronic circuits for analog signal processing, in order to deconstruct and reconfigure these study materials, creating sound narratives that result simultaneously from composition and improvisation, in which fragments of recordings Are related to noise and silence.This dissertation also presupposes a theoretical component composed by the analysis of different conceptual perspectives and performative approaches explored by other artists, with similar sound contents, within Sound Art, in order to support some of the choices made.